KEPRIBADIAN TOKOH PEREMPUAN DALAM NOVEL PERAHU KERTAS KARYA DEWI LESTARI DAN SI PARASIT LAJANG KARYA AYU UTAMI SUATU KAJIAN INTERTEKSTUAL - Afni, Nurafni; Fikri, Hasnul; Syofiani, Syofiani (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2024)
This research aims to: (1) describe the personality of the character Kugy in the novel Perahu Kertas by Dewi Lestari, (2) describe the personality of the character Saya in the novel Si Parasit Lajang by Ayu Utami, (3) describe the intertextual relationship between the personality of the character Kugy in the novel Perahu Kertas by Dewi Lestari and I am in the novel Si Parasite Single by Ayu Utami. This type of research is qualitative research using descriptive analysis methods. The data in this research is in the form of sentences and dialogue contained in the novel. The steps taken are (1) data comparison, (2) categorization, (3) presenting data with tabulation and description, and (4) interpreting to draw conclusions, and (5) reporting research results. Based on data analysis and discussion of the personality of the character Kugy in the novel Perahu Kertas by Dewi Lestari, findings were obtained based on the nine personality types of Baron and Elizabeth's theory, that the figure of Kugy is a romantic personality. Furthermore, the personality of the female character Saya in the novel Si Perasit Lajang by Ayu Utami is that the character Saya has an observer personality. Viewed from various aspects, the novels Perahu Kertas and Si Parasit Lajang in intertextual studies are character transformations, themes of love and friendship, as well as the influence of popular culture.